Ticks (Acari: Ixodidae) parasitizing endemic and exotic wild mammals in the Esteros del Iberá wetlands, Argentina - Debarbora, Valeria Natalia (2012)
Five species of ticks belonging to the genera Amblyomma, Haemaphysalis and Rhipicephalus were recorded from endemic and exotic wild mammals in the Esteros del Iberá wetlands, Argentina. Adults and immature stages of Amblyomma dubitatum were found on Hydrochoerus hydrochaeris, Sus scrofa, Axis axis and Myrmecophaga tridactyla. Larvae and nymphs of A. dubitatum were collected on Bubalus bubalis, Lepus europaeus, Monodelphis dimidiata and on the rodents Cavia aperea, Scapteromys aquaticus, Oligoryzomys flavescens and Akodon azarae. One male of Amblyomma nodosum was associated with M. tridactyla; specimens of Haemaphysalis juxtakochi were found on A. axis, S. scrofa and Mazama gouazoubira; and Rhipicephalus (Boophilus) microplus was detected on Blastocerus ichotomus. Adults of Amblyomma triste were collected on B. dichotomus, S. scrofa and H. hydrochaeris, while immatures of this tick were recorded on M. dimidiata, A. azarae, S. aquaticus, O. flavescens and H. hydrochaeris. In addition to elucidating tick-host associations, the findings of this survey are biomedically important. Although the tick fauna of Esteros del Iberá is limited, some species, such as A. triste and R. (B.) microplus, are recognized vectors of pathogenic agents infecting humans and animals. Also, a large number of the Esteros del Iberá collection records were for ticks from exotic (S.scrofa, A. axis, B. bubalis, L. europaeus) or reintroduced (M. tridactyla) mammals, suggesting that the introduction of these mammals may result in the amplification of tick populations in the study area, withpotential deleterious effects on the endemic fauna.